PENGARUH KONSENTRASI NaOH PADA SINTESIS MOLECULAR SIEVE BERBAHAN DASAR PIROPILIT - Riris Idiawati (JEAS (Journal of Educational and Applied Science), 2023)
Molecular sieve (MS) or known as molecular sieve is one of the products that is of concern to researchers today because it has the ability to filter gas or liquid more selectively. Molecular sieve consists of two large groups, namely natural molecular sieve and synthesized molecular sieve. Synthesized molecular sieve is usually processed from zeolite or kaolin rock because it contains high silica and alumina elements. Pyropillite has similarities with zeolite or kaolin where the alumina and silica content is quite high, so pyropillite rocks have the potential to be used as a basic material for making molecular sieve. In this study, pyropillite rock was taken from Sumbermanjing area, South Malang. MS synthesis was carried out by NaOH leaching method. The results obtained from the XRF test for the Al/Si ratio in MS10, MS15, and MS20 were 2.4, 2.2, and 2.3, respectively. XRD results show the formation of 3 phases in the synthesis of MS10 and MS15, namely sodalite phase with cubic crystal system, quartz phase with hexagonal crystal system, and diaspore phase with orthorhombic crystal system, while in MS20 a pure phase is formed, namely sodalite phase. The pore sizes of the BET test results produced on MS10, MS15, and MS20 are 30Å (mesopores), 542 Å (macropores), and 550 Å (macropores), respectively, while the resulting surface areas are 0.350 m2/g, 2.869 m2/g, and 1.176 m2/g. The presence of Si-O-Si bending, Si-O-Al, Si-O, Si-O normal to the plane stretching, Inner Surface Al-OH deformation, SiO-Si siloxine, H-O-H, -OH, C-H stretching, H-O-H bending water groups were determined using FTIR characterization.